Importance of Soil Classification and Soil Testing in Construction Industry - Abid Bashir Baba; Muhammad Kamal Khan; Bashar Hussein (International Journal of Scientific Research in Civil Engineering, 2022)
Nobody wants a construction project to turn out to be like the Leaning Tower of Pisa, right? Well, to prevent your construction project from being so and from worse fatal accidents, you need to get soil testing done after buying the piece of land and before beginning any construction. With roughly more than 1.5 million people involved in the construction world wide, a rate of 80 deaths per 1000 workers is observed, out of which 30-40 workers die in accidents related to trenching. Trenching accidents are extremely dangerous. Workers can suffer death or serious injury in mere minutes if caught in a trenching cave in. As the soil testing is one of the most important things to keep in mind during any construction project, however, it is the most overlooked step during the planning. The reason being the most people aren’t aware of such scientific lab testing of soil and for small residential projects and excavations, it is ignored fully. In this article we will discuss some related topics that are often overlooked, including soil classification and testing in construction particularly in excavation.
Keywords: Soil Testing; Bearing Capacity; Structures; Materials; Trenching; Cave In; Excavation